The risk of development of Lithuanian derivatives markets - Garškaitė-Milvydienė, Kristina (Journal of Business Economics and Management, 2021)
Derivative financial instruments play a very important role in financial markets, but they are seen as rather contradictory and their impact on financial markets and the stability of these markets has not been comprehensively examined. Therefore, the aim of this article is to systematise the potential risks of derivatives in the context of the past global financial crisis, and the recent situation in Lithuania. In particular, growing international tension and deteriorating economic situation, make it necessary to re-analyse the recent crisis, its causes and consequences. The 2007–2008 global financial crisis revealed the challenges and risks of derivatives and showed the tremendous impact that their imprudent use may have on the stability of a financial system. The Lithuanian economy recently joined the euro, but its macroeconomic fundamentals show certain risks. Infrastructures of the derivatives market, liquidity and an adequate supervisory framework are necessary to maintain stability.